2022
DOI: 10.3389/fnhum.2022.1062168
|View full text |Cite
|
Sign up to set email alerts
|

Value-driven modulation of visual perception by visual and auditory reward cues: The role of performance-contingent delivery of reward

Abstract: Perception is modulated by reward value, an effect elicited not only by stimuli that are predictive of performance-contingent delivery of reward (PC) but also by stimuli that were previously rewarded (PR). PC and PR cues may engage different mechanisms relying on goal-driven versus stimulus-driven prioritization of high value stimuli, respectively. However, these two modes of reward modulation have not been systematically compared against each other. This study employed a behavioral paradigm where participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…This extended training might have allowed that the competition between the target and the task-irrelevant cues especially the ones from the same sensory modality is better resolved. In fact, in a subsequent study (Antono et al, 2022), we showed that after being exposed to the intra- and cross-modal reward cues that were predictive of the delivery of the reward upon correct performance, the visual discrimination was enhanced by previously rewarded cues of both modalities. This finding supports the idea that the duration of training and the history of reward delivery may influence the way that task-irrelevant previously rewarded stimuli affect the perceptual decisions (Jahfari and Theeuwes, 2017; Jahfari et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This extended training might have allowed that the competition between the target and the task-irrelevant cues especially the ones from the same sensory modality is better resolved. In fact, in a subsequent study (Antono et al, 2022), we showed that after being exposed to the intra- and cross-modal reward cues that were predictive of the delivery of the reward upon correct performance, the visual discrimination was enhanced by previously rewarded cues of both modalities. This finding supports the idea that the duration of training and the history of reward delivery may influence the way that task-irrelevant previously rewarded stimuli affect the perceptual decisions (Jahfari and Theeuwes, 2017; Jahfari et al, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…Extending these findings, we showed that the coordination of attention and valuation may additionally occur for previously rewarded stimuli and engage higher-order sensory areas such as STS. An important direction for future studies will be to examine whether the mode of interaction between reward-, attention- and sensory-related areas holds under different contexts for instance different attentional loads and contingencies of rewards to performance (Antono et al, 2022). Our hypothesis is that the visual system will engage both attention and reward systems as resources to learn and change its plasticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, incidental reward stimuli that are linked to past rewarding experiences or predict reward magnitude independent of the performance in a task are more likely to have less dependence on task-related attentional processes. Likewise, orthogonal manipulation of reward and attention can be achieved when reward information is signalled through a stimulus feature (Baldassi and Simoncini, 2011;Garcia-Lazaro et al, 2018) or sensory modality (Pooresmaeili et al, 2014;Vakhrushev et al, 2021;Antono et al, 2022) that is distinct from the task-relevant target. Combining these, i.e., using previously rewarded stimuli that are task-irrelevant and are delivered through a different sensory modality, is likely to allow the maximum separation between the reward-related and the attentional prioritization of stimulus processing.…”
Section: Introductionmentioning
confidence: 99%
“…We draw on previous findings showing that reward stimuli from a different sensory modality (audition) can affect perception in vision (Pooresmaeili et al, 2014;Antono et al, 2022), even when cross-modal reward stimuli (auditory sounds) are irrelevant to the task at hand (i.e., visual orientation discrimination). Since there is evidence for the separation of attentional resources across sensory modalities (Duncan et al, 1997;Alais et al, 2006), these findings may indicate that cross-modal reward stimuli affect visual processing independently of visual attention.…”
Section: Introductionmentioning
confidence: 99%